In a large dataset of primary care patients, use of CHA2DS2-VA score leads to almost universal recommendation for anticoagulation in those aged 65 years and over with atrial fibrillation. (3rd October 2022) - Orchard, J; Giskes, K; Orchard, J W; La Gerche, A; Neubeck, L; Lowres, N; Freedman, B
Abstract: Background: Treatment with oral anticoagulants (OAC) for high-risk atrial fibrillation (AF) patients can reduce stroke risk by two-thirds. From 2012–14, the OAC treatment recommendation threshold in international guidelines moved from CHADS2 ≥2 to CHA2 DS2 -VASc ≥2 (men) or ≥3 (women), equivalent to a "sexless" CHA2 DS2 -VA≥2. This move aimed to identify truly low risk patients who did not need OAC treatment. General practitioners (GPs) report barriers about assessing patient suitability for OAC. Objectives: To compare the proportion of AF patients for whom OAC treatment is recommended under CHADS2 ≥2 and CHA2 DS2 -VA ≥2, and to look at the drivers of any differences, using an existing dataset. Methods: Analyses were conducted on a large Australian general practice dataset collated during previous studies (2011–2019), with deidentified data extracted from the clinical records system at a single timepoint for regularly-attending adult patients from 164 practices. CHADS2 and CHA2 DS2 -VA scores were calculated for AF patients with sufficient data available and the proportion with CHADS2 and CHA2 DS2 -VA ≥2 was compared using chi-square tests. Results: There were records for 340, 463 patients, of which 285, 635 (8, 294 with AF) had sufficient data to calculate CHADS2 and CHA2 DS2 -VA scores. Among AF patients of all ages, the CHA2 DS2 -VA ≥2 threshold captured a significantly higher proportion than CHADS2≥2 (85% vs 68%, p<0.0001). In AF patients aged ≥65 years, the CHA2 DS2 -VA ≥2 threshold also captured a significantly higher proportion than CHADS2 ≥2 (96% vs 76%, p<0.0001). Almost all older patients (≥65 years) who were captured by CHA2 DS2 -VA ≥2 but not CHADS2 ≥2 (n=1395) qualified on the basis of age, with only 1.4% eligible because of age 65–74 years and vascular disease history. Conclusions: The change from CHAD2 to CHA2 DS2 -VA has resulted in a significantly higher proportion of patients with AF being recommended OAC treatment under the guidelines, driven almost entirely by the revised scoring for age. Among AF patients aged ≥65 years, almost all (96%) were recommended OAC treatment under CHA2 DS2 -VA, demonstrating that AF is strongly associated with other vascular pathology. These findings support the Canadian guidelines, which recommend OAC treatment for all AF cases aged ≥65 years. The findings also reinforce the argument that AF screening in those aged ≥65 years is justified, as almost all patients with prevalent AF in that age group are eligible for OAC treatment. These results suggest could be an argument for simplifying the treatment message for GPs, which may reduce barriers and further improve treatment rates. High rates of associated vascular pathology in AF patients suggest that additional management strategies are also justified, including promotion of exercise, smoking cessation, and treatment of associated conditions such as hypertension and diabetes. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): RACGP Foundation / HCF Research Foundation GrantUniversity of Notre Dame Australia Research Grant